Fiscal Monitor, October 2012 : Taking Stock: A Progress Report on Fiscal Adjustment: Taking Stock: A Progress Report on Fiscal Adjustment. (Fiscal Monitor; Fiscal Monitor ;, 2012)
With growth weakening in many parts of the world and downside risks on the rise, fiscal consolidation remains challenging. However, considerable progress has been made in strengthening fiscal accounts following their sharp deterioration in 2008-09. This issue of the Fiscal Monitor takes stock of this progress, focusing on its size, composition, and implications for employment and social equity. The issue finds that most countries--and especially advanced economies--have made significant headway in rolling back fiscal deficits, but that efforts at controlling debt stocks are taking longer to yield results. The mix of revenue and expenditure policies employed by countries with sizable fiscal consolidation needs has differed, with advanced economies in general relying more on spending retrenchment than emerging markets and low-income countries. Both spending and revenue measures have important implications for employment and social equity, the issue finds, and these implications need to be taken into account if the large consolidation efforts underway are to be sustainable.